2013
DOI: 10.1111/fare.12023
|View full text |Cite
|
Sign up to set email alerts
|

Fathers' Involvement in Child Health Care: Associations with Prenatal Involvement, Parents' Beliefs, and Maternal Gatekeeping

Abstract: Using data from 182 dual-earner couples experiencing the transition to parenthood, this study examined associations between prenatal involvement, gender role beliefs, and maternal gatekeeping and new fathers’ involvement in child health care. Results indicated that prenatal father involvement was associated with both fathers’ direct engagement in child health care and fathers’ perceived influence in child health-related decision-making. Fathers also demonstrated greater direct engagement in child health care w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
75
0
14

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 109 publications
(95 citation statements)
references
References 53 publications
(70 reference statements)
6
75
0
14
Order By: Relevance
“…McBride and Rane (1998) suggested that a supportive coparenting relationship is one in which one parent encourages the other to be involved with the children (i.e., the mother encourages the father to be involved with his children). Other researchers have also found that encouragement and supportive coparenting are conceptually similar (Zvara, Schoppe-Sullivan, & Dush, 2013). Thus, in this study, we view encouragement as being synonymous with coparenting support.…”
Section: Gatekeepingsupporting
confidence: 58%
“…McBride and Rane (1998) suggested that a supportive coparenting relationship is one in which one parent encourages the other to be involved with the children (i.e., the mother encourages the father to be involved with his children). Other researchers have also found that encouragement and supportive coparenting are conceptually similar (Zvara, Schoppe-Sullivan, & Dush, 2013). Thus, in this study, we view encouragement as being synonymous with coparenting support.…”
Section: Gatekeepingsupporting
confidence: 58%
“…Furthermore, the lack of fatherly voice was disappointing. 4 Although this pattern is typical in family research, particularly among fathers of minority races (Parke et al, 2003), failing to attend to fathers' involvement in family caregiving silences this collective and subverts their role in caregiving (Zvara, Schoppe-Sullivan, & Dush, 2013). It is crucial to explore multiple family roles when assessing the development and socialization of family members (see Parke, 2004).…”
Section: Resultsmentioning
confidence: 99%
“…For example, the dynamics of feeding an infant if only the mother can directly feed can quickly change parenting roles. Even beliefs about engagement and involvement influence the possibilities of maternal gatekeeping (Zvara, Schoppe‐Sullivan, & Kamp Dush, ). These issues have several nuances, just like the other qualitative themes discussed in the book.…”
Section: Adding To the Discussionmentioning
confidence: 99%